﻿AMERICAN'S REVENGE AGAINST JAPAN IN MICHAEL BAY'S PEARL HARBOR MOVIE (2001): A SOCIOLOGICAL APPROACH - PUTERI, ANGGIET NOVIANA (2011)
This study is aimed to show American's revenge against Japan in Michael Bay's Pearl Harbor movie by using sociological approach. It is done by establishing two objectives: the first is analyzing the movie based on the sociological approach. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is Pearl Harbor movie directed by Michael Bay released in 2001. While the secondary data sources are other materials taken from books, encyclopedia, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on the structural analysis of each elements, it shows that the character and characterization, casting, plot, setting, point of view, theme, mise en scene, cinematography, sound and editing are related to each other and form the unity into good quality movie. Second, based on the sociological analysis, there is a close relationship between the movie story and the reality of American life that America takes revenge against Japan in order to heal the Americans's suffering and to get the honor back that is betrayed by Japan. This movie also shows that war just brings more harm than good no matter the purposes are.